Parathyroid Hormone Signaling in Osteocytes - Wein, Marc N (JBMR Plus, 2017)
Osteocytes are the most abundant cell type in bone and play a central role in orchestrating skeletal remodeling, in part by producing paracrine‐acting factors that in turn influence osteoblast and osteoclast activity. Recent evidence has indicated that osteocytes are crucial cellular targets of parathyroid hormone (PTH). Here, we will review the cellular and molecular mechanisms through which PTH influences osteocyte function. Two well‐studied PTH target genes in osteocytes are SOST and receptor activator of NF‐κB ligand (RANKL). The molecular mechanisms through which PTH regulates expression of these two crucial target genes will be discussed. Beyond SOST and RANKL, PTH/PTH‐related peptide (PTHrP) signaling in osteocytes may directly influence the way osteocytes remodel their perilacunar environment to influence bone homeostasis in a cell‐autonomous manner. Here, I will highlight novel, additional mechanisms used by PTH and PTHrP to modulate bone homeostasis through effects in osteocytes. © 2017 The Authors. JBMR Plus is published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research.